NATIONAL INDUSTRY 4.0 PLATFORMS IN THE VISEGRAD 4 COUNTRIES – A COMPARISON WITH THE FRONTRUNNER DIGITAL ECONOMIES IN EUROPE - GYIMESI, Áron (Studia Universitatis Babeș-Bolyai Oeconomica, 2021)
Based on the international digitization indexes, the development level of digitalization in the Visegrad Four (V4) countries is similar in many respects. The status of the recent digital developments is comparable in results and in deficits also. These economies have similar inescapable paths in the past and further development opportunities in the future. The economic success of these four countries greatly depends on the transformation of their economic structures, mainly by utilizing digitalization. This study compares the approaches, activities and initiatives of the national Industry 4.0 platforms of the V4 countries that promote and support the digital transformation on the national strategic level. The study also highlights the results that have already been achieved by the members of the European Quartet. These four countries have reached good results in digital infrastructure investments. Meanwhile, they are left behind in skillsets, education and adoption of companies, regarding their digital transformation. Beside the direct comparison of the four Industry 4.0 platforms, the study extends the research to three of the Frontrunner countries of the EU in digitalization, namely to Austria, Germany, Sweden, to understand the best practices they use and actions they take regarding the digitalization. The paper formulates guidelines for defining competitive policies and techniques for accelerating the digitalization of the V4 economies. The study lists the pain points of the V4 digitalization and makes suggestions on recoveries, mainly on the field of the potential involvement of companies and the financing of the national I40 platforms. JEL classification: O11, O14, O23, O38, O33, D83.